The stormy waters of the International Criminal Court: universal fight against impunity or liberal universalization? - Kowalski, Mateus (2014)
The universalistic dimension of the International Criminal Court's (ICC) nature and function is clear. Yet, this dimension must be thoroughly defined. We must ask ‘what universalism’? A rational approach to international social relations is different from an ethical one. While the rational approach may lead to universalization of localized specific moral models (e.g. the liberal Western model) promoting its hegemony, the ethical approach promotes diversity through considering non-reducible differences and common human phenomena in which only a minimal common ethics is universal. This paper argues that the answer to this structural question is crucial to understand if the ICC is essentially a hegemonic tool to expand the predominant Western liberal model or rather a mechanism to fight impunity acknowledging diversity and rooted on an ethical concern. We contend that the ICC is immersed in troubled waters where it is not always possible to separate a universalizing Western liberal approach from an ethical universal approach. Nevertheless, we conclude that the Court, even if partially and at times serves as tool for hegemony, is essentially defined by the universalization of the fight against impunity through reference to a minimal common ethics.